Effects of different pretreatment methods on the drying characteristics and quality of potatoes. Issue 11 (29th September 2020) - Sun, Xiangfeng; Jin, Xin; Fu, Nan; Chen, Xiaodong
Abstract: The effects of different pretreatments on the vitamin C content of peeled fresh potato, the drying characteristics, and several quality attributes of dehydrated potatoes were investigated. Citric acid pretreatment (0.1%–0.3%, 10–30 min), steam blanching (100ºC, 1–2 min), and water blanching (95°C, 1–2 min) were found to have no obvious effect on the drying rate of potatoes, whereas temperature was the main influencing factor. In terms of quality of dehydrated diced potato, 20 min of citric acid pretreatment resulted in the highest vitamin C retention and better color. Furthermore, dehydrated potato pretreated with citric acid all showed similar dynamic moisture adsorption curves, namely type II sorption isotherm. The moisture adsorption curves can be well fitted using the Guggenheim–Anderson–deBoer model with R 2 higher than .97. Abstract : In this study, the 0.2% citric acid for 20 min was the best pretreatment method, which can made drying potato obtain the better color and high vitamin C.